Textiles and clothing sustainability : recycled and upcycled textiles and fashion - Muthu, Subramanian Senthilkannan (Springer, 2016)
This book discusses in detail the concepts of recycling and upcycling and their implications for the textiles and fashion sector. In addition to the theoretical concepts, the book also presents various options for recycling and upcycling in textiles and fashion. Although recycling is a much-developed and widely used concept, upcycling is also gaining popularity in the sector.
Keywords: Textile fabrics -- Recycling.; Textile waste.; Clothing and dress -- Remaking.; elektronické knihy; electronic books